2012
DOI: 10.1534/genetics.112.145706
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane Proteins UNC-40/DCC, PTP-3/LAR, and MIG-21 Control Anterior–Posterior Neuroblast Migration with Left–Right Functional Asymmetry in Caenorhabditis elegans

Abstract: Migration of neurons and neural crest cells is of central importance to the development of nervous systems. In Caenorhabditis elegans, the QL neuroblast on the left migrates posteriorly, and QR on the right migrates anteriorly, despite similar lineages and birth positions with regard to the left-right axis. Initial migration is independent of a Wnt signal that controls later anteriorposterior Q descendant migration. Previous studies showed that the transmembrane proteins UNC-40/DCC and MIG-21, a novel thrombos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
107
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(109 citation statements)
references
References 51 publications
(95 reference statements)
2
107
0
Order By: Relevance
“…Several transmembrane proteins, DPY-19, MIG-21, UNC-40/DCC (Deleted in Colorectal Cancer), and NF-κB-inducing kinase (NIK) MIG-15, regulate the initial Q-neuroblast polarization, and mutations of these genes reduced Q-neuroblast polarization (8)(9)(10)(11). The C. elegans Wnt/β-catenin pathway activates the expression of the Antennapedia-like Homeobox(Hox) gene mab-5, which is necessary and sufficient to ensure the posterior migration of QL.a (the anterior descendant of QL) and QL.ap (the posterior descendant of QL.a) (12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Several transmembrane proteins, DPY-19, MIG-21, UNC-40/DCC (Deleted in Colorectal Cancer), and NF-κB-inducing kinase (NIK) MIG-15, regulate the initial Q-neuroblast polarization, and mutations of these genes reduced Q-neuroblast polarization (8)(9)(10)(11). The C. elegans Wnt/β-catenin pathway activates the expression of the Antennapedia-like Homeobox(Hox) gene mab-5, which is necessary and sufficient to ensure the posterior migration of QL.a (the anterior descendant of QL) and QL.ap (the posterior descendant of QL.a) (12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Although numerous molecules have been identified that act in the Q cells to promote migration, such as the transmembrane receptors UNC-40/DCC, PTP-3/ LAR, and MIG-13 (Sundararajan and Lundquist 2012;Wang et al 2013;Sundararajan et al 2015), fewer have been identified that act outside the Q cells to control their migration. Of the nonautonomous genes that have been implicated in Q-descendant migration, most are secreted molecules such as Wnts (Hunter et al 1999;Whangbo and Kenyon 1999;Korswagen 2002;Pan et al 2006) and SPON-1/F-spondin (Josephson et al 2016b), although the Fat-like cadherin CDH-4 has been demonstrated to nonautonomously affect Q-cell migration (Sundararajan et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…To score Q-cell protrusions, animals with expression of GFP in the Q neuroblasts from the egl-17 promoter (ayIs9) were synchronized to 1-2.5 hr posthatching (Chapman et al 2008;Sundararajan and Lundquist 2012). Briefly, gravid adults were allowed to lay eggs overnight.…”
Section: Scoring Q-cell and Aqr/pqr Aqr Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…We used transgenic RNAi of spon-1 driven from the myo-3, egl-17, and scm promoters to knock down spon-1 (Esposito et al 2007;Sundararajan and Lundquist 2012). Alone, Pmyo-3:: spon-1(RNAi) weakly affected AQR (1% defective) migration (Table 1).…”
Section: Spon-1 Suppresses Mab-5 Gain Of Functionmentioning
confidence: 99%